“And currently aren’t you working?”: the general structure of job interviews supporting teaching materials for Portuguese as a Host Language - Frezza, Minéia; Bordignon, Matheus; Freitas, Liélen Caroline Rodrigues de (The ESPecialist, 2025)
This article presents the results of a study that used Conversation Analysis methodology to examine the overall structure of job interviews and, consequently, develop didactic materials for Portuguese as a Host Language. The study was conducted based on eighteen audio and video recorded interviews at a National Employment System (SINE) office in southern Brazil. In this article, we present the analysis of one of these interviews, which represents the general structure of these interactions. The didactic material developed based on this study addresses interactional characteristics intrinsic to the investigated interactional context, which is highly relevant for immigrants. Those unfamiliar with the format of a job interview in Brazil will be able to obtain a detailed preview of this interactional phenomenon from this material. It is defended that immigrants receive the necessary support to establish themselves and achieve a good quality of life in the country. For this, it is essential that they have access to adequate educational materials to improve their language studies and, consequently, facilitate their social and professional integration in the country.